(untitled) (Research, Society and Development, 2021)
Hemangioma is a benign neoplasm common in the head and neck region and is characterized by an abnormal ploriferation of blood vessels, this neoplasm has a predilection for females and when it is associated with the oral and perioral regions, they can cause aesthetic and functional damage depending on your location. The aim of this study was to present a clinical case of oral hemangioma, to discuss the importance of adequate diagnosis as well as ways of treatment for a safe and cautious intervention of this pathology. Case report: Female patient, 54 years old, leucoderma, housewife, attended the Dentistry clinic, with the main complaint of a blackened lesion on the lower lip and without systemic involvement. Under the procedure of vitro pressure, ischemia produced by the glass plate was observed and, according to the blood collection inside, the diagnostic hypothesis of hemangioma was considered. Observing the vascular nature of the hemangioma, the choice was made not to perform the biopsy due to the high chance of bleeding. The treatment performed by injection of the sclerosing solution of monoethanolamine oleate promoted the involution of the lesion.